Room‐Temperature Lasing of Dual‐Metal Nanoparticle Surface Lattice Resonance with Monolithic InGaAs Multiple Quantum Wells on GaAs Substrates - Wen‐Hsuan Hsieh; Chia‐Jui Chang; Cheng‐Ching Li; Kuo‐Ping Chen; Jhih‐Sheng Wu; Chia‐Yen Huang; Tien‐Chang Lu (Advanced Photonics Research)
This study demonstrates the surface lattice resonance (SLR) laser utilizing asymmetric dual‐metallic nanoparticle arrays, incorporating a high‐refractive‐index material, which exhibits a confinement factor of 16%, enhancing the coupling between metal and dielectric materials. Multiple quantum wells (MQWs) are integrated with plasmonic SLR in the proposed structure. Through theoretical design and experimental validation, the MQW plasmonic SLR laser exhibits excellent high Q‐factor and stable operation at room temperature. This demonstration enhances laser performance and achieves low‐threshold operation with a laser threshold as low as ≈2.39 MW cm−2. This study's design of plasmonic SLR lasers further advances the realization of optoelectronic device applications.